O dever de fundamentação das decisões judiciais - Francesconi, Thaís Regina Henrique (2019)
This paper approaches the duty of justification of judicial decisions. This responsability - besides being a guarantee underlying the Democratic State based on the rule of law and provided for in the legal system since the Luso-Brazilian law - grew in prominence with its positivation in the Federal Constitution of 1988 and, recently, with new rules established by the Brazilian Code of Civil Procedure (CPC) of 2015. The objective of this study is to ascertain if there has been a significant improvement of the duty of justification in view of what is laid down in art. 11, caput, and, above all, in paragraphs of § 1 of art. 489 of CPC/2015 in order to determine whether such legal provisions may or may not contribute to the fairness of decisions. In order to test this hypothesis, an investigation was carried out based in specific legal literature, anchored on a historicallegislative, doctrinal and jurisprudential research. In addition to presenting general considerations about the justification and approaching it both as a fundamental norm of the Civil Procedure and as an essential element of the sentence, the study assesses all subsections of § 1 of art. 489 of CPC/2015. Besides addressing the legislation and related doctrine, it also deals with judicial decisions rendered before and after the new Code had entried into force. The paper concludes that the caput of art. 11 and the subsections of § 1 of art. 489 of CPC/2015 represent a major step so that judicial decisions set out the reasons for deciding on the concrete case which was brought before the Judiciary and not before any other, in order that those decisions can be fairer